Women's education, contraception use, and high-risk fertility behavior: A cross-sectional analysis of the demographic and health survey in Ethiopia - Woldeamanuel, Berhanu Teshome; Gessese, Getachew Tilahun; Demie, Takele Gezahegn; Handebo, Simegnew; Biratu, Tolesa Diriba (Frontiers in Global Women's Health, 2023)
Background High-risk fertility behavior (HRFB) among women is the main factor in a wide range of detrimental effects on both the mother's and the child's health, which has an impact on both the mother's and the child's survival. Early childbearing is associated with a higher number of live births and may result in poorer maternal, baby, and child health outcomes. Infant and child mortality are also linked to short birth intervals and higher birth order. Thus, this study aims to examine the link between women's education, contraception use, and high-risk fertility behavior in Ethiopia. Methods Data was drawn from the 2019 Ethiopian Interim Demographic and Health Survey. The analysis covered a total of 5,846 women. The effect of predictor variables on HRFB was quantified using multivariable logistic regression analysis. At a 95% CI of the odds ratio excluding one, a significant association between the HRFB and predictor variables was observed. Results About 72.8% (95% CI 71.6%–73.9%) of women experience high-risk fertility behaviors. Of these, 32% experience single high-risk fertility behavior, and 40.8% experience multiple high-risk fertility behaviors. Of those who experience high-risk fertility behaviors, 58.7% have birth orders of more than three, 22.4% have short birth intervals (less than 24 months); 35.1% are old (over 34 years old); and 1.6% are young (less than 18 years old). Women with no education (AOR = 4.31; 95% CI: 2.09, 8.89) and primary education only (2.71; AOR = 2.71; 95% CI: 1.63, 4.50) are more likely to engage in high-risk fertility behaviors than women with a higher level of education. Every additional year of schooling reduces the odds of high-risk fertility behavior by 6% (AOR = 0.94; 95% CI: 0.89, 0.98). The use of modern contraception (AOR = 0.74; 95% CI: 0.622, 0.879) and knowledge of modern contraception methods (AOR = 0.80; 95% CI: 0.66, 0.96) reduce the risk of HRFB. Conclusions Primary education and a lack of education significantly raise the risk of HRFB. However, in Ethiopia, the risk of experiencing HRFB is reduced through modern contraceptive methods, awareness of modern contraceptive methods, and years of education. All initiatives to decrease maternal and newborn mortalities by reducing the risk of HRFB should educate women and encourage them to use modern contraception.